Nectar chemistry is not only a plant's affair: floral visitors affect nectar sugar and amino acid composition. Issue 7 (16th May 2021) - Bogo, Gherardo; Fisogni, Alessandro; Rabassa‐Juvanteny, Joan; Bortolotti, Laura; Nepi, Massimo; Guarnieri, Massimo; Conte, Lucia; Galloni, Marta
Abstract : Floral nectar is the primary reward directly consumed by floral visitors and its chemical composition affects their behaviour and fidelity. In turn, floral visitors are expected to alter floral nectar composition directly or indirectly through the introduction of external contaminants, such as pollen grains and microorganisms. To understand the effect of exogenous factors on nectar chemistry, we investigated the modifications of nectar sugar and amino acid composition in relation to floral visitors in the perennial herb Gentiana lutea . We quantified nectar contamination by floral visitors through visitor exclusion experiments in the field, estimating pollen and yeast concentration in visited flowers and in uncontaminated nectar at two different flower stages (flower bud and older open flowers). We then assessed changes in the composition and concentration of sugars and both protein and non‐protein amino acid in the nectar. We found clear differences in the chemical composition of flower nectar in relation to flower stage and floral visitation. Nectar sugar and amino acid concentrations were significantly higher in older flowers than in flower buds. In addition, nectar sugar concentration was significantly higher in older flowers where visitors were excluded than in visited flowers. On the contrary, amino acid concentration was comparable between visited and non‐visited older flowers. We also found that pollen contamination enriched the amino acid profile of the host nectar both quantitatively and qualitatively. Finally, nectar exposed to floral visitors showed a higher number of yeast cells than unvisited flowers although too low to cause the observed changes in the glucose:fructose ratio, suggesting the presence of fructose‐related bacteria. Our results show that the chemical composition of floral nectar is altered by several endogenous and exogenous factors in a complex process of ecological relations, and suggest that the modulation of floral visitation through nectar is not solely related to the plant itself.